Four years into MACRA: What has changed?. Issue 1 (7th January 2020) - Cheng, Jonathan; Kim, Jackson; Bieber, Scott D.; Lin, Eugene
Abstract: In 2015, Congress passed the Medicare Access and CHIP Reauthorization Act (MACRA), a policy intended to transition Medicare away from pure fee‐for‐service care to value‐based care. MACRA does this by evaluating the cost and quality of providers, resulting in financial bonuses and penalties in Medicare reimbursement. MACRA offers two tracks for participation, the Merit‐based Incentive Payment System and the Advanced Alternative Payment Models. Although the payment rules are different for each of the tracks, common to both is an emphasis on holding providers accountable for high‐quality, cost‐efficient care. Early data suggest that the End‐stage renal disease Seamless Care Organizations, an Advanced Alternative Payment Model, resulted in cost‐savings concurrent with improved care quality. Additionally, on July 10th 2019, the President signed an executive order that further attempts to improve kidney disease care by shifting its focus away from in‐center hemodialysis toward chronic kidney disease care, home‐based dialysis, kidney transplantation, and innovating new therapies for kidney disease. These changes to nephrology reimbursement present a unique opportunity to improve patient outcomes in a cost‐effective way. A multidisciplinary effort among policy makers, nephrology providers, and patient advocacy groups is critical to ensure these changes in care delivery safeguard and improve patient health.